Socio-physical and Health Conditions of Person with Disability in Nepal - Raut, Rekha (ILAM इलम, 2024)
Disability is a complex multidimensional condition and poses a number of challenges for measurement. This study seeks to identify the issues and challenges on disabilities management and socio economic and demographic aspects of person with disability. Similarly, this study has also explored the health problems and economic opportunities of disable people of Bhaktapur district. This study is based in Bhaktapur district and concentrate to person with disability. Primary data was collected from the field study through sourcing at study side. Sampling procedure is Census and quantitative nature of data was collected through questionnaire and interviews tools. Conclusion of this study is disabling people are living with low socio economic and poor health condition. Descriptive research design was used in this study. In the study side just 97 persons with disability are recorded at the study time. Among 97 respondents nearly 15% are involved in service. Only 36.84% are literate and 97.89% of the respondents get treatment received against disability. 63.16% of the respondents are not participating in social activities because of disability. Out of 97 respondents, 35(46.06%) are not engaging in economic activities Findings of this study is that, they are denied access to essential services. People with disabilities are greater risk of being neglected and excluded from their family. It is imperative for the government to ensure access to education and healthcare services for all citizens. Additionally, the government should adapt policies to ensure equal opportunities for the disabled in economic participation, thereby improving their socio-economic status.